Penggunaan media pembelajaran permainan monopoli untuk meningkatkan kemampuan menulis pantun peserta didik kelas v sdn banyuanyar 1 tahun ajaran 2024/2025 - Santi Mustika Wati; Retno Winarni (Universitas Sebelas Maret, 2025)
Abstract. This study aims to describe the use of monopoly game learning media to improve the ability to write pantun of grade V students of SDN Banyuanyar 1, explain the obstacles and solutions, and describe the results of improving the ability to write pantun. The subjects of this study were grade V teachers and 28 students. Data collection involved tests and non-tests, while data analysis followed the Miles and Huberman model data reduction, presentation, conclusion drawing, and verification. The use of monopoly game learning media to improve the ability to write pantun has obstacles faced by students, one of which is being less active in learning activities. Improvements that can be made based on these obstacles are that teachers create interesting learning media so that students remain focused on learning. The ability to write pantun has increased from cycle 1 and cycle 2 by 89%.